2023
DOI: 10.1186/s12936-022-04435-9
|View full text |Cite
|
Sign up to set email alerts
|

Transmission efficiency of Plasmodium vivax at low parasitaemia

Abstract: Background Plasmodium vivax is responsible for much of malaria outside Africa. Although most P. vivax infections in endemic areas are asymptomatic and have low parasite densities, they are considered a potentially important source of transmission. Several studies have demonstrated that asymptomatic P. vivax carriers can transmit the parasite to mosquitoes, but the efficiency has not been well quantified. The aim of this study is to determine the relationship between parasite density and mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Specifically, we found that during standard CQ-PQ treatment, the median number of gametocytes on D3 was significantly higher among CPR mutated allele carriers. Of importance, the median of 0.9 gametocytes/µL found among these patients is in the range of the recently determined lowest infective P. vivax gametocyte density: 0.2 to 5 gametocytes/µL, with a median of 0.8 gametocytes/µL ( 37 ). This contrasts with the significantly lower median of 0.06 gametocytes/µL reported for the CPR wild-type carriers, a value markedly below the documented lower limit for effective infectivity.…”
Section: Discussionmentioning
confidence: 51%
“…Specifically, we found that during standard CQ-PQ treatment, the median number of gametocytes on D3 was significantly higher among CPR mutated allele carriers. Of importance, the median of 0.9 gametocytes/µL found among these patients is in the range of the recently determined lowest infective P. vivax gametocyte density: 0.2 to 5 gametocytes/µL, with a median of 0.8 gametocytes/µL ( 37 ). This contrasts with the significantly lower median of 0.06 gametocytes/µL reported for the CPR wild-type carriers, a value markedly below the documented lower limit for effective infectivity.…”
Section: Discussionmentioning
confidence: 51%